Protective Effect of Nigella sativa Seed Extract on Alloxan-Induced Mice Kidney Histology - Hotimah Salim; Evi Sylvia Awwalia; Ilham Putera Alam (WMJ (Warmadewa Medical Journal), 2022)
Abstract Nigella sativa (N. sativa) has been used in traditional medicine, and several studies have been performed in the last decades to reveal its effects of it on different medical disorders such as diabetes, dyslipidemia, hypertension, and obesity. This study aimed to evaluate the effects of Nigella sativa extract in an alloxan-induced mice model. This research was a true experimental post-test-only control group design. Eight-weeks old male Mus musculus were treated with alloxan (150 mg/ kg) by a single intraperitoneal injection to induce diabetes mellitus. At three days of injection, N. sativa extract (150 and 300 mg/kg) was administered via gavage for two weeks. The result of this study showed that N. sativa seed extract had a significant (P<0.05) nephroprotective effect on the kidneys based on the degree of kidney damage in alloxan-induced mice. This effect may be due to Nigella sativa’s antioxidant properties. Keywords: Nigella sativa, histology kidney, oxidative stress